Tindak Pidana Aborsi Akibat Perkosaan - Ni Putu Ratih Puspitasari; I Made Sepud; Ni Made Sukaryati Karma (Warmadewa Press, 2021)
Abortion is an abortion wherein in an abortion in the body there is a fetus but it is not perfectly shaped. According to the Criminal Code the abortion is prohibited for any reason, but the Health Law provides exceptions if medical indications. The problem is how is the regulation of the crime of abortion? And what are the criminal sanctions against perpetrators of criminal acts of abortion due to rape? The type of research used is normative legal research, with a legal and conceptual problem approach. Legal material comes from primary and secondary legal materials; the technique of collecting legal materials is by reviewing the laws and regulations governing abortion. Analysis of descriptive legal material analysis and adjusting to legal arguments. The regulation of abortion in the Criminal Code is regulated in article 346 of the Criminal Code, 347 of the Criminal Code, 348 of the Criminal Code and 349 of the Criminal Code. While the regulation of abortion in the Health Law is regulated in Articles 75, 76, 77 and Article 194 of Law No. 36 of 2009 concerning Health. Sanctions for abortion offenders can be subject to articles in the Criminal Code, namely Article 346 subject to a maximum sentence of four years in prison. Where as in article 347-349 the Criminal Code can be imprisoned for a maximum of fifteen years. In the Health Law, the maximum criminal threat is 10 years and a maximum fine of Rp. 1,000,000,000.00 (one billion rupiah). Conclusion, if the abortion is done not because of medical indications, then the act of abortion can be claimed as a crime.